Back to the future: Agent-based modelling and dynamic microsimulation - Matteo Richiardi; Justin van de Ven; Patryk Bronka (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2023)
In this chapter we focus on the commonalities and differences between agent-based and dynamic microsimulation analytical approaches. Starting from a shared history, we discuss how the two literatures quickly diverged. Discussion concludes with evidence of some recent convergence between agent-based and dynamic microsimulation methods, and emerging opportunities for mutual reinforcement of the two methodologies.
Keywords: 330